2020
DOI: 10.1186/s10194-020-01166-7
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to late-life migraine diagnoses and risk of dementia: a national register-based follow-up study

Abstract: Background: Previous studies found an association between migraine and dementia, which are two leading causes of disability. However, these studies did not differentiate between migraine types and did not investigate all prevalent dementia subtypes. The main objective of this national register-based study was to investigate whether migraine was a risk factor for dementia. Additionally, we explored potential differences in dementia risk for migraine with and without aura. Methods: We obtained data on birth coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
4
36
1
Order By: Relevance
“…Similar to our study, a Danish cohort study included patients with migraine with a primary diagnosis before the age of 59 years [26]. This study demonstrated a higher rate of dementia events in patients with migraine than in those without migraine [26]. Moreover, it is generally accepted that the increased cardiovascular risk of migraine is a composite effect of multiple parameters, such as hypertension, diabetes mellitus, obesity, and dyslipidaemia [27][28][29][30].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar to our study, a Danish cohort study included patients with migraine with a primary diagnosis before the age of 59 years [26]. This study demonstrated a higher rate of dementia events in patients with migraine than in those without migraine [26]. Moreover, it is generally accepted that the increased cardiovascular risk of migraine is a composite effect of multiple parameters, such as hypertension, diabetes mellitus, obesity, and dyslipidaemia [27][28][29][30].…”
Section: Discussionsupporting
confidence: 71%
“…However, contrary to other previous studies, we did not include only older patients-we included patients with migraine who were aged over 55 years. Similar to our study, a Danish cohort study included patients with migraine with a primary diagnosis before the age of 59 years [26]. This study demonstrated a higher rate of dementia events in patients with migraine than in those without migraine [26].…”
Section: Discussionsupporting
confidence: 69%
“…The risk of developing dementia after age 60 was higher among individuals with migraine in midlife than among individuals without [21]. Therefore, aging can be identi ed as a key factor that increases the incidence of dementia [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, this proposition related only to migraines with aura. Another study found that, because changes in the brain indicated that cerebral small vessel disease increases the risk of most dementia types and cerebrovascular dysfunction, the vascular factors of migraine may be related to the risk of dementia [21]. Yet another study determined that acupuncture at the Buihui (GV20) and Yintang (GV29) points increased the CBF of the prefrontal lobe and hippocampus in mouse models of Alzheimer's disease [38].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ]. A Danish national register-based follow-up study conducted between 1935 and 1956 hypothesized that patients reporting migraine in midlife are likely to experience cognitive decline later in their life [ 12 ]. In a population-based longitudinal study, an age and gender-specific pattern has been found.…”
Section: Reviewmentioning
confidence: 99%